Scalable Synthesis of Switchable Assemblies of Gold Nanorod Lyotropic Liquid Crystal Nanocomposites. Issue 22 (25th April 2019) - Liu, Xiao; Qi, Genggeng; Park, Albert Min Gyu; Rodriguez‐Gonzalez, Arnaldo; Enotiadis, Apostolos; Pan, Wenyang; Kosma, Vasiliki; Fuchs, Gregory D.; Kirby, Brian J.; Giannelis, Emmanuel P.
Abstract: A new class of solvent free, lyotropic liquid crystal nanocomposites based on gold nanorods (AuNRs) with high nanorod content is reported. Application of shear results in switchable, highly ordered alignment of the nanorods over several centimeters with excellent storage stability for months. For the synthesis, AuNRs are surface functionalized with a charged, covalently tethered corona, which induces fluid‐like properties. This honey‐like material can be deposited on a substrate and a high orientational order parameter of 0.72 is achieved using a simple shearing protocol. Switching shearing direction results in realignment of the AuNRs. For a film containing 75 wt% of AuNRs the alignment persists for several months. In addition to the lyotropic liquid crystal characteristics, the AuNRs films also exhibit anisotropic electrical conductivity with an order of magnitude difference between the conductivities in direction parallel and perpendicular to the alignment of the AuNRs. Abstract : A new class of solvent‐free, lyotropic liquid crystal nanocomposites based on gold nanorods, with high nanorods content is reported. Application of shear results in switchable, highly ordered alignment of the nanorods over several centimeters with excellent storage stability for months, which also results in anisotropic electrical conductivity with an order of magnitude difference.